Helical Piles Embedded in Expansive Soil Overlaying Sandy Soil - Al-Busoda, Bushra Suhale; Abbase, Hassan Obaid (Al-Khwarizmi Engineering Journal, 2017)
In this study, the behavior of square helical piles models (5×5) mm2 embedded in expansive soil bed overlaying a layer of sandy soil was investigated. The sand layer 200mm thickness was compacted into four sub layers in a steel container with diameter 400mm in size. Sandy soil layer was compacted into two relative densities 40% and 80%. The bed of ثءحties 40% and 80%.The bed of o00mm in size.Sandy soil layer was compacted into two relative densities 40% and 80%.The bed of oexpansive soil 300mm thickness was compacted into six sub layers on sandy soil layer. Model tests are performed with helical pile length 350mm, 400mm and 450mm and with helix diameter 15mm and 20mm. Also, one helix and double helix were used for these piles. Water was allowed to seep from bottom of sandy soil to reach surface of expansive soil through four sand drains around helical pile. This study revealed that the upward movement of helical piles decreases with increasing depth of embedment in the sandy layer, helix diameter and number of helix. The increase in these parameters provides anchorage against uplifting. Helical piles embedded in sandy soil of relative density (40%) have uplift movement more than helical piles of relative density (80%).